2013
DOI: 10.1111/nmo.12106
|View full text |Cite
|
Sign up to set email alerts
|

Electrical tissue impedance spectroscopy: a novel device to measure esophageal mucosal integrity changes during endoscopy

Abstract: Electrical tissue impedance spectroscopy is a new tool that can be used to evaluate esophageal mucosal integrity changes during endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…In vivo and in vitro parameters of esophageal mucosal integrity were measured as previously described ( 10,20 ). Briefl y, electrical tissue impedance spectroscopy was performed at 5 cm proximal to the gastro-esophageal junction.…”
Section: Assessment Of Esophageal Mucosal Integritymentioning
confidence: 99%
“…In vivo and in vitro parameters of esophageal mucosal integrity were measured as previously described ( 10,20 ). Briefl y, electrical tissue impedance spectroscopy was performed at 5 cm proximal to the gastro-esophageal junction.…”
Section: Assessment Of Esophageal Mucosal Integritymentioning
confidence: 99%
“…4 Recently, a new endoscopically placed probe has been developed that may measure epithelial impedance over a 2-cm area. 5 By measuring current generated by ion flow, this device provides a measure of transepithelial resistance and permeability because there are no ion transporters in the esophageal epithelium. By using a through-the-scope MI measurement device we recently showed the clinical utility of MI measurement in differentiating gastroesophageal reflux disease (GERD) from non-GERD.…”
mentioning
confidence: 99%
“…The development of a flexible impedance probe was first reported in 2003 by Jones et al [22]. Lundin et al [23] demonstrated that morphological changes in the esophageal mucosa could be discerned by the use of bioimpedance spectroscopy in animal models, and Weijenborg et al [24] reported that extracellular impedance measured using ETIS was significantly lower in patients with GERD than in controls, with strong inverse correlations between extracellular impedance determined using ETIS and DIS and between extracellular resistance and TEER. The ETIS probe is 3.2 mm in diameter and has four electrodes at the tip (Medical Engineering Section, Royal Hallamshire Hospital, Sheffield, UK).…”
Section: Electrical Tissue Impedance Spectroscopymentioning
confidence: 99%
“…Moreover, these 2 resistors represent resistance of the extracellular and intracellular compartments, and the capacitator reflects the capacitance of the membrane. Using this principle, the ETIS probe is thought to be able to measure extracellular and intracellular impedances separately [24]. Recently, Weijenborg et al [25] reported that extracellular MI measured using the ETIS probe did not differ between patients with NERD and those with FH.…”
Section: Electrical Tissue Impedance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation